Pengaruh Financial Distress, Thin Capitalization dan Capital Intensity Terhadap Tax Avoidance - Teuku Andre Ravanelly; Mulyadi Noto Soetardjo (UNKLAB Business School, 2023)
This research is conducted to observe, examine, and analyze the effect of financial distress, thin capitalization, and capital intensity on the practice of tax avoidance. This research uses secondary data from companies in the manufacturing sector (basic industry and chemical, consumer goods industry dan miscellaneous industry) listed on the IDX for a period of 3 years, from 2018 – 2020 (200 firm years). The technique for selecting sample utilizes purposive sampling method and data is analyzed using multiple regression model. The results of this study indicate that financial distress has a positive effect on tax avoidance, thin capitalization has a positive effect on tax avoidance and capital intensity has a negative effect on tax avoidance in manufacturing companies listed on the IDX during 2018-2020. Keyword(s): Tax Avoidance, Financial Distress, Thin Capitalization, Capital Intensity Penelitian ini dilaksanakan dengan tujuan untuk mengamati, meneliti dan menganalisis pengaruh dari financial distress, thin capitalization dan capital intensity terhadap praktik penghindaran pajak (tax avoidance). Penelitian ini menggunakan data-data sekunder dari perusahaan manufaktur dalam basic industry and chemical, consumer goods industry dan misccelaneous industry yang terdaftar dalam BEI selama periode pengamatan 3 tahun yakni dari tahun 2018 – 2020 (200 observasi). Teknik dalam mengumpulkan sampel menerapkan metode purposive sampling dan dianalisis menggunakan metode regresi berganda. Hasil penelitian ini menunjukkan bahwa financial distress berpengaruh positif terhadap tax avoidance, thin capitalization berpengaruh positif terhadap tax avoidance dan capital intensity berpengaruh negatif terhadap tax avoidance pada perusahaan manufaktur yang terdaftar di BEI selama tahun 2018-2020. Kata kunci: Tax Avoidance, Financial Distress, Thin Capitalization, Capital Intensity